S. JOHNSON'S DICTIONARY GUIDE AS AN EXPRESSION OF THE DICTIONARY IDEA - U. B. Rakhmonov (Journals Park Publishing, 2025)
This article is based on the materials of the famous American lexicographer Samuel Johnson's dictionary. In this article “Plan of the English dictionary” was analyzed. This “Plan” was written in 1746, served as the basis for “A Brief Prospectus for the Construction of a New Dictionary of the English Language”.
Keywords: Plan, US lexicography, academia, mistakes, prospectus, language refinement.